Solid mass falling into the reservoirs shallow water equations validity from the engineering point of view - Freitas Maciel, G. [UNESP] (My University, 1998)
Water waves generated by a solid mass is a complex phenomenon discussed in this paper by numerical and experimental approaches. A model based on shallow water equations with shocks (Saint Venant) has developed. It can reproduce the amplitude and the energy of the wave quite well, but because it consistently generates a hydraulic jump, it is able to reproduce the profile, in the case of high relative thickness of slide, but in the case of small relative thickness it is unable to reproduce the amplitude of the wave. As the momentum conservation is not verified during the phase of wave creation, a second technique based on discharge transfer coefficient α, is introduced at the zone of impact. Numerical tests have been performed and validated this technique from the experimental results of the wave's height obtained in a flume.
Keywords: Computer simulation; Discharge (fluid mechanics); Hydraulic jump; Mass transfer; Mathematical models; Numerical methods; Reservoirs (water); Discharge transfer coefficient; Shallow water equations; Slides; Water waves